Integrasi Fitur Notifikasi Pemesanan untuk Meningkatkan Pelayanan Pengguna pada E-Commerce Batik Wistara - Sutanto, Aqila Murodah; Rizky Parlika; Teguh Sutanto (Jurnal Komtika (Komputasi dan Informatika), 2026)
Batik Wistara is a Micro, Small, and Medium Enterprise (MSME) that sells various types of fabrics both offline and through its e-commerce website. In practice, the admin often struggles to keep up with online orders because most of the work is still centered on offline sales. As a result, some orders are noticed late, which slows down the response to customers and affects service quality. To help overcome this problem, this study develops an automatic notification system that connects directly to WhatsApp and Telegram using an API. With this system, every new order is sent to the admin in real time, allowing them to immediately see and respond to incoming transactions. The development process follows the waterfall method, starting from identifying needs, designing the API flow, implementing the system, and finally testing its performance. The results show that this feature makes the admin’s workflow more efficient because online orders are no longer dependent on manually checking the dashboard. Notifications arrive instantly, helping the admin maintain service consistency and avoid missed orders. This study also offers practical insight for other MSMEs that want to strengthen their e-commerce operations by adopting API-based notification solutions